2020
DOI: 10.1108/aia-02-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between facial emotion recognition and cognitive flexibility in autism spectrum disorder

Abstract: Purpose Various studies have examined the role of executive functions in autism, but there is a lack of research in the current literature on cognitive flexibility in autism spectrum disorders (ASD). The purpose of this study is to investigate whether cognitive flexibility deficits could be related to facial emotion recognition deficits in ASD. Design/methodology/approach In total, 20 children with ASD and 20 typically developing children, matched for intelligence quotient and gender, were examined both in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In addition, we showed that social communication, which was enhanced by the treatment, was significantly associated with emotion recognition, an essential skill for social interaction that previous studies have shown is deficient in individuals with ASD [4,60]. Notably, CF is associated with emotional recognition in healthy children [61] as well as in people with ASD [17], as emotion recognition has been shown to require flexible reasoning strategies in response to a situation [62]. In other words, our results may imply that tDCS with left dlPFC cathode placement and right supraorbital region anode placement and concurrent "cold" EF cognitive remediation training may promote flexible problem solving.…”
Section: Clinical and Cognitive Effects Of Prefrontal Tdcs With Concu...mentioning
confidence: 65%
See 1 more Smart Citation
“…In addition, we showed that social communication, which was enhanced by the treatment, was significantly associated with emotion recognition, an essential skill for social interaction that previous studies have shown is deficient in individuals with ASD [4,60]. Notably, CF is associated with emotional recognition in healthy children [61] as well as in people with ASD [17], as emotion recognition has been shown to require flexible reasoning strategies in response to a situation [62]. In other words, our results may imply that tDCS with left dlPFC cathode placement and right supraorbital region anode placement and concurrent "cold" EF cognitive remediation training may promote flexible problem solving.…”
Section: Clinical and Cognitive Effects Of Prefrontal Tdcs With Concu...mentioning
confidence: 65%
“…Importantly, a number of studies J o u r n a l P r e -p r o o f have demonstrated that CF deficits are associated with impaired social interaction skills such as emotion recognition, given emotion recognition is regarded as "hot" EF (i.e., EF that involves affective processing; [12]). For example, using a variant of the Wisconsin Card Sorting Test (WCST), Fabio et al [17] showed that the performance of children with ASD decreased after the card sorting rule had changed, and this impaired performance was positively correlated with impaired emotion recognition abilities. Moreover, Strang et al [18] showed that slower performance on the Trail Making Test (which involves rule switching) significantly correlated with more inflexible behaviors in daily life.…”
mentioning
confidence: 99%
“…However, this could represent overstimulation, and it is well-known that sensory overstimulation is a serious problem for many children with ASD [ 16 ]. Moreover, NAO cannot express facial emotions, and this may not be helpful for children with difficulties in recognizing human facial emotional expressions [ 1 , 2 , 17 ]. For this reason, a robot cannot appear both extremely human-like and socially simple [ 14 ].…”
Section: Social Humanoid Commercial Robotsmentioning
confidence: 99%
“…Additionally, the study showed a correlation between facial recognition, sensory perception, attention, and memory. 30 Hyper-emotional arousal in ASD children causes emotional dysregulation and cognitive impairment. 31 Emotional arousal governs both positive and negative reactions and is more associated with ER memory.…”
Section: Introductionmentioning
confidence: 99%